The adeno-associated virus rh10 vector is an effective gene transfer system for chronic spinal cord injury - Yutaka Hoshino (Nature Portfolio, 2019)
Abstract Treatment options for chronic spinal cord injury (SCI) remain limited due to unfavourable changes in the microenvironment. Gene therapy can overcome these barriers through continuous delivery of therapeutic gene products to the target tissue. In particular, adeno-associated virus (AAV) vectors are potential candidates for use in chronic SCI, considering their safety and stable gene expression in vivo. Given that different AAV serotypes display different cellular tropisms, it is extremely important to select an optimal serotype for establishing a gene transfer system during the chronic phase of SCI. Therefore, we generated multiple AAV serotypes expressing ffLuc-cp156, a fusion protein of firefly luciferase and Venus, a variant of yellow fluorescent protein with fast and efficient maturation, as a reporter, and we performed intraparenchymal injection in a chronic SCI mouse model. Among the various serotypes tested, AAVrh10 displayed the highest photon count on bioluminescence imaging. Immunohistological analysis revealed that AAVrh10 showed favourable tropism for neurons, astrocytes, and oligodendrocytes. Additionally, with AAVrh10, the area expressing Venus was larger in the injury epicentre and extended to the surrounding tissue. Furthermore, the fluorescence intensity was significantly higher with AAVrh10 than with the other vectors. These results indicate that AAVrh10 may be an appropriate serotype for gene delivery to the chronically injured spinal cord. This promising tool may be applied for research and development related to the treatment of chronic SCI.